Demographic analysis of Reward preference in the Social Security Commisssion - Elago, Else (School of Management Studies, 2024)
Workplace demographics and a shortage of skills have obligated organisations to recognize rewards influence the retention of skilled employees, as homogenous retention policies are no longer suitable (Pregnolato, 2010). The goal of this study is to generate an understanding of the total rewards that the employees of the Social Security Commission (referred to hereunder as SSC) deem important for their retention and motivation or employee engagement, as well as to find the ideal mix and the preferred value of rewards that preserve employees from numerous demographic groups, in the context of the SSC – referring specially race, gender, age groups and education levels. In order to endure the battle for talent, it is essential to recognize the rewards that employees prefer employees. This is particularly appropriate in Namibia where the demographics of the workplace is evolving and distinguished retention schemes are desirable to retain employees from various groups (Pregnolato, 2010). A quantitative research design using a descriptive approach was adopted. Convenience sampling was utilised for the online survey whereby it was distributed to all employees of the SSC. The study revealed that SSC workforce is composed of majority of females of Generation Y and black people, with a diploma occupying non-managerial positions, with 1-11 years of experience in SSC. Overall, within the six reward categories, regardless of demographics, the most preferred remuneration options are leadership management development programmes, promotions in present business unit, base salary directed at the higher end of the market and retention bonus, employer that pays 100% to total retirement fund of employees including the maximum medical aid coverage, short-term incentives connected to their performance including shares or stock options (Pregnolato, 2010). Gaining knowledge in this regard will direct the SSC in drafting and amending well-informed and science-based reward strategies and policies. No account of literature exists which classifies the preferred reward combination and the number of rewards that retain employees (Pregnolato, 2010). The current study identified the ideal mix of total rewards that retain skilled workers as well as employees from diverse age groups, gender and race. Keywords: benefits, motivation, recognition, remuneration, retention, rewards.